Enhanced Emotional Memory: Cognitive and Neural Mechanisms. (December 2013) - Talmi, Deborah
Memory for emotional events is typically more vivid and accurate than memory for neutral ones. The modulation model focuses on the consolidation of memory traces to provide a partial account of enhanced emotional memory. Mediation theory focuses on encoding and retrieval to explain the selective enhancement of memory for emotional aspects of a complex event and why emotional memory also can be enhanced immediately after the experience, before consolidation has occurred. Mediation theory can therefore complement the modulation model, and together they may provide a more comprehensive account of human emotional memory.